Presentase Jenis Makanan Dalam Lambung Ikan Lais (Ompok hypopthalmus) Di Rawa Sungai Rungan, Kota Palangka Raya - Lukas Lukas; Infa Minggawati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2014)
Fish Lais (Ompok hypopthalmus) is one of the fish that live in the waters of the river swamp Rugan, Palangkaraya. Type of food and the availability of food in the water will determine the distribution of fish Lais. Total composition of the food supply will also determine the species composition of fish in the waters and eventually also will affect the growth of fish. The purpose of this study was to determine the percentage and type of food in the stomach Lais fish caught in the river swamp Rungan Palangkaraya city. This study was carried out for 4 months, from January to April 2014, samples were taken every month Lais fish, fish caught and dissected to identify the contents of the stomach, the type of food in the stomach of fish Lais expressed in percent. The results showed that the type of fish food Lais for January are: fish = 60%, not identified = 31%, insects = 9%. Month of February 2014 kinds of food are insects = 56, = 22% shrimp, fish = 11% and = 11% unidentified. March 2014, the type of food is fish = 48%, insects = 36%, 16% and not identified for April Lais percentage of fish food is insects = 73%, not identified = 26%, fish = 1%. Water quality in the river swamp waters are pH between 4.5 to 6 Rungai, 1.7 to 5.1 m water depth, DO 32-36 mg / l, and the water temperature 26 - 27oC.